Identification of Training Needs to Foster a Research Culture in Indonesian Schools Davao Philippines - Rusilowati, Ani; Marwoto, Putut; Astuti, Budi; Babiera II, Rene M.; Nada, Nadila Qotrun; Aini, Zahrotul (Universitas Negeri Semarang, 2024)
Research skills need to be possessed by students in the era of educational revolution 4.0 and society 5.0. The efforts that have been made to apply a scientific approach still have not maximized research skills for students. An independent curriculum with a new learning paradigm enables the achievement of student research skills and a research culture in schools can be realized. These skills should also be possessed by Indonesian students in other countries, including those at the Indonesian School of Davao (SID)-Philippines. Therefore, it is necessary to carry out dissemination regarding learning that can foster a research culture, through activities carried out together with teachers at SID. This step is a form of educational reform that can help teachers prepare their students to compete at the global level. A research culture can be realized through the application of the Differentiate Indirect Learning (Dif-In-Le) learning model with a Science, Technology, Engineering and Mathematics (STEM) approach. The agreed activity plan is training. However, because there was a restructuring of school principals, the activity was changed to a brainstorming with the Indonesian Consulate General in Davao attended by Filipino SID teachers. The aim of this service activity is to identify the needs of SID teachers regarding innovative learning. An innovative learning model was introduced that can foster a research culture for students and schools, namely Dif-In-Le STEM approach. As a result of identifying needs, it was found that an introduction to Indonesian culture was needed for Indonesian children living in Davao, Philippines.